A RANDOMIZED STUDY OF CARDIAC RHYTHM PATTERNS IN YOUNG ADULTS EXPOSED TO ACADEMIC STRESS: Life Science-Physiology - SEEMA GOYAL; JOHN PRAMOD MD (International Journal of Life Science and Pharma Research, 2013)
Electrocardiogram (ECG) is one of the frequently used screening tools to rule out possible cardiac anomalies in an otherwise healthy young adult proposed to be inducted into a job, training or an academic course requiring reasonably good semblance of body systems dependant on efficient cardiovascular functioning. Several factors are known to change action potential in cardiomyocytes reflecting the same in an ECG. Some of these factors like gender specificity, academic or physical stress are generally overlooked while interpreting ECG especially at the time of recruitment. Commonest changes observed are those pertaining to rate or rhythm parameters which may either be benign or may reveal a potentially dangerous cardiac anomaly which has remained silent so far. The aim of the present study was to assess changes in ECG parameters of young medical students as they undergo various phases of their academic year. Our study reveals that most changes are confined to rate and rhythm patterns and are consistent with expected physiological gender variations and magnitude of the stress level. None of the observed changes required intervention or further investigation as they were all within the homoeostatic limits having transient or insignificant impact on cardiac functioning.